Hypertensive Stroke in Bangladesh: Demographic Insights from a Hospital-Based Study - Mohammad Nazrul Islam; Md Alamgir Kabir; AKM Kamruzzaman (Journal of Shaheed Suhrawardy Medical College, 2026)
Background: Stroke remains one of the leading causes of morbidity, mortality, and long-term disability worldwide. It poses a particularly high burden in low- and middle-income countries such as Bangladesh, where limited access to preventive healthcare, lack of awareness, and poor control of hypertension significantly contribute to disease prevalence. Hypertension, the most common modifiable risk factor, is responsible for nearly two-thirds of stroke cases in the Bangladeshi population. Despite medical advances, the demographic characteristics of hypertensive stroke patients in this region remain underexplored, highlighting the importance of population-based data for designing effective prevention strategies. Objective: The present study aimed to assess the demographic profile of hypertensive patients presenting with stroke at a tertiary care hospital in Sylhet, Bangladesh, in order to identify the age, sex, occupational, and socio-economic patterns associated with stroke occurrence in this high-risk group. Methods: A cross-sectional observational study was conducted over a one-year period among 96 hypertensive patients admitted with clinically and radiologically confirmed stroke in the Department of Medicine and Neuromedicine at Sylhet M.A.G. Osmani Medical College Hospital. Data were collected through a structured, pre-tested questionnaire covering demographic variables such as age, gender, occupation, socio-economic status, smoking habits, and family history of hypertension or stroke. Descriptive statistics including frequency, percentage, mean, and standard deviation were used for analysis. Results: The mean age of participants was 60 ± 11.46 years, ranging from 30 to 80 years, with the highest incidence among individuals aged 51–60 years (34.4%). Females comprised 68.8% of the study group. Housewives (59.4%) and farmers (21.9%) were the most affected occupations, while 55.2% of patients belonged to the lower-middle socio-economic class. A positive family history of hypertension was observed in 44.8% of cases, and 15.6% were smokers. Conclusion: Stroke primarily affected middle-aged to elderly hypertensive females from lower socio-economic backgrounds. These findings underscore the urgent need for targeted community-based screening, public health education, and effective blood pressure management programs to reduce the growing burden of stroke in Bangladesh. J Shaheed Suhrawardy Med Coll 2024; 16(2): 16-19